САЎЫН СЫЙЫРЛАРДЫҢ СҮТИНЕ ТӘСИР КӨРСЕТИЎШИ СЫРТҚЫ ФАКТОРЛАР - Казакбаев, Б. (SCIENCE and SOCIETY, 2017)
The article deals with the issues of development of the branch of stock-breeding and increasing the product's quality in farming and personal subsidiary facilities. The author gives recommendations how to organize contents and feeding and deal with tribe work in cattle breeding.
Keywords: pasture region; meat - milk products; strong stern base; tribe’s deal; zooengineerung service